An Improved Method for the Diatom Test Utilizing DNA Binding Ability of Silica1. Issue 3 (6th February 2014) - Seo, Yasuhisa; Ichida, Daisuke; Sato, Shingo; Kuroki, Kohji; Kishida, Tetsuko
Abstract In order to devise a better forensic test for diatoms, the DNA binding ability of the diatom frustule constructing by silica, in the presence of chaotropic ions were utilized. It was proved that the diatoms were able to be captured via λDNA using silica‐coated magnetic beads (Mag beads), followed by isolation and purification from the Mag beads as a solid phase by substituting the chaotropic agent with ultrapure water. Five cases of drowning, three in freshwater and two in seawater, were applied to the present method and similar results as the usual diatom test were obtained. Specimens of lung and other organs were rendered clearly visible, with elimination of foreign impurities. The present method appears applicable for detection of diatoms indirectly using PCR amplification of bound DNA or directly staining of the DNA.